The riskology of the material in urban space - Kataev, Dmitrii Valentinovich; Epifanov, Aleksandr Olegovich (Урбанистика, 2024)
The article considers the possibilities of integrating the theory of urban risk assessment (URA – Urban Risk Assessments), the concept of spatial syntax (Space syntax), the three-pronged strategy of risk management and compliance (GRC Governance, Risk and Compliance) in the paradigmatic optics of «turning to the material» (TTM) in social research devoted to the analysis and management of risks in urban space. A look at the risks of the urban environment through the prism of TTM allowed to specify the spatial framework of the Space syntax concept, covering the boundaries of a city or district. By overcoming the distinction between acting subjects and objective structures in the TTM in relation to the theory of URA, the functional positions of counting and evaluating possible risk situations are determined. The specifics of applying the «Turn to the material» to the concept of Governance, Risk and Compliance solves the problem of choosing a risk mitigation management strategy. Such a theoretical synthesis is explicated on the example of the urban space of Lipetsk. The operationalization of concepts, including the identification of environmental, social, technological and other risks on the basis of concepts modified through TTM, has determined the tools for integrated monitoring and forecasting of urban space risks. The allocation of material objects as new participants enriched the traditional theories of riskology, adding material dimension and accounting for interaction with material objects. It has become possible to create more accurate and differentiated urban risk management strategies. Consideration of Lipetsk as a case study makes it possible to specify the proposed methodologies and emphasize their applicability in the real conditions of the urban environment. The use of URA made it possible to identify the main categories of risks for the city, such as environmental, social and technological threats.